2011
DOI: 10.1007/s10546-011-9611-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Diurnal Cycle in the Atmospheric Boundary Layer Over Land as Represented by a Variety of Single-Column Models: The Second GABLS Experiment

Abstract: We present the main results from the second model intercomparison within the GEWEX (Global Energy and Water cycle EXperiment) Atmospheric Boundary Layer Study (GABLS). The target is to examine the diurnal cycle over land in today's numerical weather prediction and climate models for operational and research purposes. The set-up of the case is based on observations taken during the Cooperative Atmosphere-Surface Exchange Study-1999 (CASES-99), which was held in Kansas, USA in the early autumn with a strong diur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
203
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(219 citation statements)
references
References 53 publications
14
203
1
1
Order By: Relevance
“…A possible explanation is that, to avoid numerical instability potentially resulting from thermal decoupling of the surface and atmosphere, operational models tend to overestimate the level of background turbulence in very stable conditions. This is a common problem for climate models as well (Tjernström et al, 2005), and was also revealed in the Global Energy and Water Cycle Experiment (GEWEX) Atmospheric Boundary Layer Study (GABLS) experiments (Cuxart et al, 2006;Steeneveld et al, 2006;Svensson et al, 2011).…”
Section: Discussionmentioning
confidence: 81%
“…A possible explanation is that, to avoid numerical instability potentially resulting from thermal decoupling of the surface and atmosphere, operational models tend to overestimate the level of background turbulence in very stable conditions. This is a common problem for climate models as well (Tjernström et al, 2005), and was also revealed in the Global Energy and Water Cycle Experiment (GEWEX) Atmospheric Boundary Layer Study (GABLS) experiments (Cuxart et al, 2006;Steeneveld et al, 2006;Svensson et al, 2011).…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, measurements and simulations of the diurnal cycle on land show that the ABL is non-neutral most of the day. [1] In addition, measurements of offshore wind farmswhere seasonal variations are more pronounced than daily variations -indicate that for the low wind speed range (i.e. less than 15 m s -1 ), non-neutral atmospheric stability is prevailing as well.…”
Section: Introductionmentioning
confidence: 99%
“…The mixing layer begins to develop after sunrise due to the increased turbulent fluxes associated with surface-absorbed solar radiation and heating (Medeiros et al, 2005;Liu and Liang, 2010). The value of h reaches its maximum during the late afternoon over land (Liu and Liang, 2010;Bianco et al, 2011;Svensson et al, 2011). Comparing Fig.…”
Section: Climatology Of Mixing Layer Height Overmentioning
confidence: 96%